EVENT-DRIVEN PROGRAMMING FOR HIGH THROUGHPUT APPLICATIONS - Raghukishore Balivada (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Event-driven programming has emerged as a transformative paradigm in modern software architecture, particularly for high-throughput applications requiring optimal performance and responsiveness. This comprehensive article explores the fundamental principles, advantages, and practical applications of event-driven programming in contemporary distributed systems. The article examines core operational mechanisms, including non-blocking operations, asynchronous event processing, and event loop architectures, while comparing traditional threading models with event-driven approaches. Through detailed analysis of real-world implementations, the research demonstrates how event-driven architectures significantly improve system performance, resource utilization, and scalability across various domains, including real-time applications, GUI systems, and microservices architectures. The article also covers best practices, error-handling strategies, resource management techniques, and testing methodologies essential for successful event-driven system implementations.